Overexpression of particular MADS‐box transcription factors in heat‐stressed plants induces chloroplast biogenesis in petals. (19th November 2018) - Wang, Zhen; Shen, Yuxiao; Yang, Xiao; Pan, Qi; Ma, Guangying; Bao, Manzhu; Zheng, Bo; Duanmu, Deqiang; Lin, Rongcheng; Larkin, Robert M.; Ning, Guogui
Abstract: Chloroplasts convert solar energy into biologically useful forms of energy by performing photosynthesis. Although light and particular genes are known to promote chloroplast development, little is known about the mechanisms that regulate the tissue‐specificity and cell‐specificity of chloroplast biogenesis. Thus, the mechanisms that determine whether non‐photosynthetic plastids rather than chloroplasts develop in petals remain largely unexplored. Although heat stress is known to inhibit photosynthesis, we do not know whether heat stress affects chloroplast biogenesis. Here, we report that heat stress up‐regulates the expression of chlorophyll biosynthesis‐related genes and promotes chloroplasts biogenesis in petals overexpressing SOC1 (suppressor of overexpression of CO) and novel SOC1 ‐ like genes. We also found that these specific MADS‐box transcription factors are present in most photosynthetic eukaryotes and that the expression of more than one homolog is observed in chloroplast‐containing tissues. These findings not only provide novel insights into the tissue specificity of chloroplast biogenesis and a method for producing green petals but also are consistent with heat stress influencing chloroplast biogenesis in higher plants. Abstract : Mechanisms that control the tissue specificity of chloroplast biogenesis are poorly understood. We found that overexpressing genes encoding particular MADS‐box transcription factors up‐regulate the expression of chlorophyll biosynthesis‐related genes and promote chloroplasts biogenesis in the petals of heat‐stressed plants. These findings provide novel insight into the mechanisms that control the tissue specificity of chloroplast biogenesis and a method for producing green petals.